Israel’s Strategic and Tactical Use of the 2017 Maccabiah Games for Nation Branding and Public Diplomacy - Yoav Dubinsky; Lars Dzikus (Journal of Applied Sports Management, 2019)
The Maccabiah Games, also known as “The Jewish Olympics,” are a quadrennial international multisport event that takes place in Israel and is deeply rooted in the Zionist movement. The purpose of this study is to analyze strategies and tactics Israel used in the 2017 Maccabiah Games for nation branding and public diplomacy. Based on ethnographic field research during the Maccabiah Games in July 2017, the authors identified nine different tactics used by the Maccabiah organizations that correlate the strategic goals of the State of Israel. Results have theoretical and practical implications of how countries can use sports events for nation branding and public diplomacy. Subscribe to JASM
Keywords: Maccabiah Games; Israel; nation branding; public diplomacy